Mapping legal authority for terrestrial conservation corridors along streams - Stahl, Amanda T.; Fremier, Alexander K.; Cosens, Barbara A. (Conservation biology, 2020)
Wildlife corridors aim to promote species’ persistence by connecting habitat patches across fragmented landscapes. Their implementation is limited by patterns of land ownership and complicated by differences in the jurisdictional and regulatory authorities under which lands are managed. Terrestrial corridor conservation requires coordination across jurisdictions and sectors subject to site‐specific overlapping sources of legal authority. Mapping spatial patterns of legal authority concurrent with habitat condition can illustrate opportunities to build or leverage capacity for connectivity conservation. Streamside areas provide pragmatic opportunities to leverage existing policy mechanisms for riverine and terrestrial habitat connectivity across boundaries. Conservation planners and practitioners can make use of these opportunities by harmonizing actions for multiple conservation outcomes. We formulated an integrative, data‐driven method for mapping multiple sources of legal authority weighted by capacity for coordinating terrestrial habitat conservation along streams. We generated a map of capacity to coordinate streamside corridor protections across a wildlife habitat gap to demonstrate this approach. We combined values representing coordination capacity and naturalness to generate an integrated legal‐ecological resistance map for connectivity modeling. We then computed least‐cost corridors across the integrated map, masking the terrestrial landscape to focus on streamside areas. Streamside least‐cost corridors in the integrated, local‐scale model diverged (∼25 km) from national‐scale least‐cost corridors based on naturalness. Spatial categories comparing legal‐ and naturalness‐based resistance values by stream reach highlighted potential locations for building or leveraging existing capacity through spatial coordination of policy mechanisms or restoration actions. Agencies or nongovernmental organizations intending to restore or maintain habitat connectivity across fragmented landscapes can use this approach to inform spatial prioritization and build coordination capacity. Article impact statement: Combined mapping of legal authority and habitat condition reveals capacity to coordinate actions along streams for clean water and wildlife. Mapeo de la Autoridad Legal para los Corredores Terrestres de Conservación a lo Largo de Ríos Stahl et al. Resumen Los corredores de fauna buscan promover la persistencia de las especies al conectar los fragmentos de hábitat a lo largo de paisajes fragmentados. Su implementación está limitada por los patrones de propiedad de tierras y se complica con las diferencias entre las autoridades jurisdiccionales y regulatorias que las administran. La conservación por corredores terrestres requiere de coordinación entre las jurisdicciones y los sectores sujetos a fuentes de autoridad legal que se traslapan y que son específicas del sitio. El mapeo de los patrones espaciales de la autoridad legal simultánea a la condición del hábitat puede ilustrar oportunidades para construir o hacer uso de la capacidad para la conservación por conectividad. Las áreas adyacentes a los cauces fluviales proporcionan oportunidades prácticas para hacer uso de los mecanismos políticos existentes para la conectividad de hábitats ribereño y terrestre a través de las fronteras. Los planificadores y practicantes de la conservación pueden usar estas oportunidades al armonizar las acciones para múltiples resultados de conservación. Formulamos un método integrativo orientado por los datos para mapear las múltiples fuentes de autoridad legal ponderadas por la capacidad para coordinar la conservación de hábitats terrestres a lo largo de ríos. Generamos un mapa de la capacidad para coordinar los corredores de protección a lo largo de los vacíos en los hábitats de fauna para demostrar esta estrategia. Combinamos los valores por medio de la representación de la capacidad de coordinación y la naturalidad para generar un mapa de resistencia legal y ecológica para el modelado de la conectividad. Después, computamos los corredores de menor costo en todo el mapa integrado, enmascarando el paisaje terrestre para enfocarnos en las áreas adyacentes al cauce fluvial. Los corredores de menor costo adyacentes a los cauces dentro del modelo integrado de escala local difirieron (∼25 km) de los corredores de menor costo basados en la naturalidad a escala nacional. Las categorías espaciales que compararon los valores de resistencia basada en la legalidad y en la naturalidad por alcance del río resaltaron las localidades potenciales para la construcción o el uso de la capacidad existente por medio de la coordinación espacial de los mecanismos de política o de las acciones de restauración. Las agencias y organizaciones no gubernamentales con la intención de restaurar o mantener la conectividad del hábitat en un paisaje fragmentado pueden utilizar esta estrategia para informar la priorización espacial y construir la capacidad de coordinación. 摘要 野生动物廊道旨在通过连接破碎景观中的栖息地斑块来提高物种的续存, 但其建设受限于土地所有制模式, 还会因管理土地的管辖及监管机构不同而更加复杂。陆地廊道保护需要多个司法管辖区和各地受到多种法定权威管制的部门之间的协调。将法定权威的空间格局与栖息地条件的分布地图相叠加, 将有利于开展廊道连接度保护的能力建设及利用。河流沿岸地区为现有的跨境河流及陆地栖息地连接度的相关政策机制的应用提供了实践机会。保护规划者和实施者可以利用这些机会协调多方行动以取得各方面的保护成效。我们制定了一个综合的、基于数据驱动的方法, 可以将协调河流沿岸陆地栖息地保护的能力作为权重来绘制多个法定权威来源的地图。为了演示这个方法, 我们绘制了一张协调跨越野生动物栖息地空缺地带的河流沿岸廊道保护力地图。我们将代表协调能力和自然特性的数值相结合, 生成了一张用于连接度建模的法律‐生态抵抗力综合地图。随后, 我们忽略陆地景观, 将重点放在河流沿岸地区, 计算了整个综合地图的最低成本廊道。结果显示, 由局部尺度的综合模型得到的河流沿岸最低成本廊道与基于自然特性的国家尺度最低成本廊道偏离约 25 公里。河流沿岸基于法律和自然特性抵抗力比较的空间分类进一步展示了可以通过政策机制或恢复行动的空间协调来建设和利用现有能力的潜在地点。计划恢复或维持破碎景观之间的栖息地连接度的机构或非政府组织可以应用这种方法确定优先保护的空间并建立协调力。【翻译: 胡怡思; 审校: 聂永刚】